2019
DOI: 10.1002/acr.23593
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance and Depression Symptoms Mediate Relationship Between Pain and Cognitive Dysfunction in Lupus

Abstract: Even after controlling for disease activity and perceived stress, the relationship between pain and CD was explained by sleep disturbance and depression symptoms. Although these relationships need validation in longitudinal studies with additional measurement modalities, our findings may indicate promising, non-pharmacologic intervention avenues for SLE patients with pain and CD. Specifically, cognitive-behavioral therapies for depression and sleep are known to reduce distress and enhance functioning across va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 39 publications
1
22
0
2
Order By: Relevance
“…Furthermore, resilience could partially mediate the relationship between sleep disturbance and PSD. It was found that sleep disturbance contributed the most to PSD in this study, which was in agreement with most previous studies showing that sleep disturbance was positively associated with depression in patients with heart disease (48), lupus (49), and chronic obstructive pulmonary disease (50). PSD is the most common clinical complication and sequelae of stroke, studies have shown that the levels of IL-6, IL-1β, and Hcy in patients with PSD are significantly higher than those in the normal population (51).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, resilience could partially mediate the relationship between sleep disturbance and PSD. It was found that sleep disturbance contributed the most to PSD in this study, which was in agreement with most previous studies showing that sleep disturbance was positively associated with depression in patients with heart disease (48), lupus (49), and chronic obstructive pulmonary disease (50). PSD is the most common clinical complication and sequelae of stroke, studies have shown that the levels of IL-6, IL-1β, and Hcy in patients with PSD are significantly higher than those in the normal population (51).…”
Section: Discussionsupporting
confidence: 93%
“…Besides, more scholars have paid attention to anxiety and depression in SLE patients. Moreover, previous study 23 found that fragmented sleep and depression can increase the incidence of CD. And only depression levels, among clinical variables, significantly predicted cognitive performance by multivariate analysis.…”
Section: Discussionmentioning
confidence: 92%
“…Irrespective of the origin of the symptoms, current treatment recommendations for fibromyalgia in SLE are similar to those of primary fibromyalgia and include graded exercise, improvement in restorative sleep, cognitive and behavioral therapy for underlying mood disorders, and pharmacologic therapies directed at depression and neuropathic pain (43–46). Aerobic exercise has demonstrated safety and efficacy for alleviating fatigue and depression in patients with SLE (47–49).…”
Section: Discussionmentioning
confidence: 99%